If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 6x = -2 Solving -6 + 6x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6x = -2 + 6 Combine like terms: -6 + 6 = 0 0 + 6x = -2 + 6 6x = -2 + 6 Combine like terms: -2 + 6 = 4 6x = 4 Divide each side by '6'. x = 0.6666666667 Simplifying x = 0.6666666667
| 12+u=19 | | 6.2x+6-2.2x=2 | | 8.3+8.3+8.3+8.3= | | -6=-5z-6 | | -2+3=-5 | | 2x-9=24-21x | | z/6+3=z/5+2 | | .80(D-100)=D-50 | | m/4=m/12+8/3 | | 18x-25x=1/3 | | .80(D-100)=D-100 | | (9/16)/(7/10) | | 9/16/7/10 | | 2x^4-5x^3-x^2-5x-3=0 | | 56=7(24-x) | | y-6=-5x+50 | | 4(v+2)=6v+12 | | 2x-4=3(x+1) | | 8x^2-6x+10=0 | | (z/2)^2 | | -72=-6y | | 4t-5/-9=7 | | 3/7-k/3=8/21 | | -21+p=4 | | y/3=y/7+4 | | x+y=95 | | x/2-x=2 | | 7/12x=-4/36 | | -5/12y=-2/5 | | p/-4=-44 | | 7z=1/7 | | 4/2m-m=4+1/2m |